Indicadores de desenvolvimento social no Brasil - Cunha, Telma Gonçalves (2014)
In many ways that can be used to promote country s development usually appears basic themes such as education and health as priorities in the strategic plan, which would be natural considering models like the pyramid of needs / motivations of Maslow. In Brazil, as developing country, still appears illness in that direction as well as in other sectors of basic infrastructure as shown by a series of indicators. In this context, the primary objective of this research is to search among different social development indicators in Brazil, which would be the most relevant at regional and local level to examine the country. For this purpose statistics analysis were performed by using platform of 2013 Atlas Brazil provided by the United Nations Program for Development (UNDP) which contains information about the 5565 Municipalities and the Federal District. The issues raised were (i) which are the relationships between the indicators within each seven dimensions used in Atlas, in order to reduce the dimensionality of data (ii) which are the most significant to detect differences among the five regions of the country and (iii) at the local level, which of these indicators would be most critical to detect differences between the states, which could be used for planning and monitoring state. Among the results found critical indicators are observed: (1) the relevance of the population is still below the level of extreme poverty, (2) the importance of the high illiteracy rate of adults and (3) the lowest percentage of income earned by 20 % of the poorest as the most important indicators in distinguishing between regions and states of Brazil